Will It Fly? Adoption of the road pricing framework to manage drone use of airspace. (August 2021) - Merkert, Rico; Beck, Matthew J.; Bushell, James
Highlights: We adopt the theoretical road pricing framework to examine user charging potential in air drone use. Responses from 825 active drone flyers were analysed using a random parameters logit model. WTP of $0.11 for flying a drone in a safe and orderly manner for one hour was found. Modelling also shows much higher WTPs for various currently prohibited activities (e.g. fly at night) A LAAM system with variable user charges is preferred and fairer than flat registration fees/taxes. Abstract: Applications and demand for airborne drone operations, including urban air mobility, are growing rapidly in regional and metropolitan areas. However, the expected traffic volumes in cities will make it impossible to operate drones in uncontrolled airspace. Despite the wealth of literature on pricing transport infrastructure usage showing that variable pricing is the optimal way for charging for road use, jurisdictions are reluctant to move towards this efficient mechanism evident in the slow uptake of road pricing implementation globally. What is worse, regulations have been drafted to tax the drone growth similarly to cars proposing the adoption of annual registration fees for drones. This paper proposes that drone use should instead adopt a pricing structure modelled on road user charging, and presents evidence suggesting that a case can be made for enabling controlled and fair growth through low altitude airspace management (LAAM) systems and variable drone user charges. A stated preference experiment with 825 respondents who actively fly drones has shown user charge potential in way of willingness to pay (WTP) of A$0.11 for flying a drone for one hour. Random parameters logit models further allowed us to establish much higher WTP for various currently not permitted activities such as A$7.09 to fly beyond line of flight or A$4.29 to fly outside daylight hours. As such, if those occasional uses are variably charged, we argue that a commercially viable LAAM system could be implemented, and low altitude air traffic user charging could overtake implementation of the wider (i.e. road) transport capacity pricing on the fast lane.